2009
DOI: 10.1093/gerona/glp153
|View full text |Cite
|
Sign up to set email alerts
|

Age Differences in Energy Absorption in the Upper Extremity During a Descent Movement: Implications for Arresting a Fall

Abstract: During a descent movement that simulates fall arrest, the energy-absorbing capacity of the upper extremities in older women is nearly half that of young women. Absorbing the full energy of a fall in the upper extremities is a challenging task even for healthy young women. Strengthening of upper extremity muscles should enhance this ability and presumably reduce the risk for injury to the hip and head during a fall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 25 publications
3
32
0
Order By: Relevance
“…Upper-limb strength (and movement speed) should be assessed carefully in the older adult who presents with a fall-related injury, and adults should be encouraged across their lifespan to engage in exercises to strengthen upper limbs to improve their ability to stop a fall. 23 As previously mentioned, future research should also examine the potential benefit for older adults of carefully designed training based on martial arts falling techniques. 31 In the long-term care setting, the high rate of cognitive and physical impairment among residents creates challenges for widespread implementation of exercise programs, and attention should focus additionally on the design of safer environments.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Upper-limb strength (and movement speed) should be assessed carefully in the older adult who presents with a fall-related injury, and adults should be encouraged across their lifespan to engage in exercises to strengthen upper limbs to improve their ability to stop a fall. 23 As previously mentioned, future research should also examine the potential benefit for older adults of carefully designed training based on martial arts falling techniques. 31 In the long-term care setting, the high rate of cognitive and physical impairment among residents creates challenges for widespread implementation of exercise programs, and attention should focus additionally on the design of safer environments.…”
Section: Resultsmentioning
confidence: 99%
“…Although we cannot identify why hand impact was generally ineffective in halting downward movement and preventing head impact, likely causes include ineffective arm placement; nonoptimal muscle tone or muscle activation at impact; 28 and insufficient strength in upper-limb, neck and trunk muscles, 22,23 which is amenable to improvement through resistance training.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Further, it has been shown that grip strength remains up to 12 % lower at the injured site [16]. Thus, the muscle-bone interaction in the upper extremity may play an important role in determining bone strength [15,16], while also contributing to the ability of the upper extremity to absorb impact forces from a fall impact [17,18].…”
Section: Introductionmentioning
confidence: 99%